(untitled) (Research, Society and Development, 2021)
In this study, response surface methodology based on simplex- centroid design was used to optimize the gluten-free bread formulation with rice flour and cassava starch as independent variables. Bread formulations were evaluated by physicochemical analysis and descriptive sensory analysis encompassing appearance, structure, texture, and aroma parameters by a trained sensory panel. The five formulations composition showed statistical differences concerning aw, lipid and protein content. Carbohydrate was significantly correlated with specific volume and lipids with protein. Overall, rice flour’s addition improved lipid and protein, whereas further rises in cassava starch allowed developing bread with higher specific volume and sensory scores. The optimum combinations of the variables to maximize scores of porosity, texture, elasticity, and protein content, should be obtained with 51.75% of rice flour and 48.25% of cassava starch. The use of the simplex-centroid design and the response desirability function in the optimization was useful for evaluating the influence and potential of the binary mixture of rice flour and cassava starch on the sensory quality and chemical characteristics of gluten-free bread. These research findings open the scope for further investigation of rice flour and cassava starch and their useful application in gluten-free bread processing.